A combined method for gas-bearing layer identification in a complex sandstone reservoir - Xing, Donghui; Fan, Yiren; Lu, Hongfeng; Lu, Cheng; Zhang, Peng; Li, Hui; Ding, Yi (Frontiers in Earth Science, 2022)
Langgu Depression is a mature oil and gas exploration area with complicated lithology and physical properties. The varying formation fluid, low-resistivity hydrocarbon-bearing reservoirs, and non-uniform logging series greatly increase the difficulty of gas reservoir identification. The Monte Carlo method is employed to simulate the neutron-gamma logging responses to gas saturation and the influential factors. According to the result, a new gas identification chart eliminating the influence of porosity and formation water salinity is proposed to identify gas reservoirs in the old wells. At the same time, a fluid factor extracted from array acoustic logging and core measurement data is sensitive to the development of gas-bearing layers and useful for the identification of gas reservoirs in the new wells with array acoustic logging. The field examples show that the new combined method greatly improves the ability to identify gas-bearing layers and works well in old wells re-examination and new wells interpretation.